Integrating project-based learning and virtual kitchen: a digital learning innovation to enhance students’ creativity and entrepreneurial potential in bakery courses - Ifnalia Rahayu; Yuliana Yuliana; Wiwik Gusnita; Wiki Lofandri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The demand for innovative approaches in vocational education has increased significantly in the digital era. This study explores the integration of Project-Based Learning (PjBL) with a Virtual Kitchen platform to enhance students’ creativity and entrepreneurial potential in bakery courses. Using a quasi-experimental pretest-posttest design with non-equivalent groups, the research involved 52 students divided into experimental (n = 26) and control (n = 26) groups. The intervention combined project-based tasks with virtual kitchen simulations, allowing students to experiment with recipes, simulate product branding, and practice digital marketing in a risk-free environment. Data were collected through creativity assessments, product evaluation rubrics, entrepreneurial attitude scales, and student feedback surveys. Statistical analysis using paired and independent t-tests revealed a significant improvement in both creativity and entrepreneurial readiness in the experimental group (p < 0.001). The findings highlight that integrating PjBL with Virtual Kitchen not only supports technical mastery but also nurtures digital micro-entrepreneurship and innovative thinking. This model presents a transformative strategy for preparing vocational students for the demands of Industry 4.0. Recommendations are provided for further implementation in other culinary domains and the development of more advanced virtual platforms.